Materials science and technology :a comprehensive treatment /. Volume 3A, Electronic and magnetic properties of metals and ceramics Part 1 / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol editor : K. H. Jurgen Buschow - Buschow, K. H. Jurgen
Vol 3A. Electronic and magnetic properties of metals and ceramics Part 1 in 1992